Biopsy of recurrent nasolacrimal duct obstruction using sheath-guided dacryoendoscopy. (2nd January 2019) - Ueda, Kosuke; Watanabe, Akihide; Yokoi, Norihiko; Sugimoto, Manabu; Fukuoka, Hideki; Shinomiya, Katsuhiko; Kinoshita, Shigeru; Rajak, Saul; Selva, Dinesh
ABSTRACT: Purpose : The purpose of this article is to present a novel technique, as well the histopathological findings, of dacryoendoscopic guided nasolacrimal duct (NLD) biopsy for recurrent nasolacrimal duct obstruction (NLDO). Methods : This study involved subjects with recurrent NLDO. Direct endoscopic probing or sheath-guided endoscopic probing was used for the initial intubation in all treated eyes, and the stent had been removed at between 2 and 11 months (mean 3.5 months) post-intubation with dacryoendoscopic confirmation of patency and mucosal regeneration. Biopsy specimens were obtained by scraping the recurrent lesion by sheath advancement. Histopathological examination and immunohistochemical (IHC) staining were performed. Results : In five patients (two males and three females, mean age: 71.2 ± 5.6 years [range: 61–78 years]) with recurrent NLDO, biopsy specimens were obtained from six ducts of six eyes, and stratified epithelium and a mixed inflammatory cell infiltrates were identified. IHC staining was positive for cytokeratin (CK)4 and CK13, and negative for paired box protein Pax-6. Conclusions : This novel technique enabled a minimally invasive biopsy of the NLD to be obtained, and IHC staining indicated the presence of mucus epithelium, thus suggesting squamous metaplasia of the usual respiratory epithelium which likely occurs secondary to chronic inflammation.